Greeting skills: A systematic review of the literature. (17th October 2022) - Hickey, Carleana R.; Reeve, Sharon A.; Reeve, Kenneth F.; Deshais, Meghan A.
Abstract: Individuals with disabilities often demonstrate difficulty in social communication skills such as greetings. Studies have shown that deficits in greetings may negatively affect social interactions and vocational opportunities. Therefore, previous research has evaluated a variety of teaching procedures to increase greetings for individuals with disabilities with varying efficacy. This review of the literature provides an overview of studies to date in which greetings were taught to individuals with intellectual disabilities. A variety of teaching procedures were identified, and implications of those procedures are discussed. Results suggest that multiple teaching procedures may be effective; however, component analyses, further replication, and modified generalization procedures are necessary. Implications for future researchers include identifying a technological definition of greetings and evaluating effective teaching procedures and generalization strategies. Implications for practitioners include teaching one greeting type at a time, limiting the number of social skills taught simultaneously, identification of effective teaching procedures and generalization considerations.